Poverty in the Developing Countries: A multifold curse - Asrar, Zaeema; Raza, Hasan; Aslam, Muhammad Farrukh (Archives of Business Research, 2017)
As poverty is a systematic curse that affects many macro factors of economy, policies & planning not only in developing countries but throughout the world therefore it becomes a socioeconomic issue on national & international level and requires an effective framework. The purpose of the study is to identify the reasons of poverty & implications of allocated assistance by IMF & WB in the developing countries and exploring the responsiveness of international efforts to minimize the level of poverty. World Bank (WB) in the collaboration of IMF (International Monetary Fund) works for the international goal to reduce poverty through its planning & projects, provides aids to those countries that are economically weak or they are stabilizing their performances to improve their economy and controls it by SAP (Structural Adjustments Program).However, these aids & assistance are affected by political powers, corruption and mismanagement in developing countries and mostly it could not reach to allocated area that helps poverty to sustain. The study focuses on theoretical mechanics of poverty in the light of structural adjustments program and emphasizes on the need of effective governance and state citizen relationship. The result of descriptive analysis explained that aids & assistance do not reach to the deserving one because of political vested interests and corruption or spur inequality. These aids reach optimal levels only if there will no preferred creditor notions, state will be committed & responsible and good governance will also be required to reduce poverty with the help of unanimous efforts